Increased BMI favors weaning in patients with chronic intestinal failure due to short bowel syndrome: a retrospective cohort study in Italy - Merlo, Fabio Dario; Jeppesen, Palle Bekker; Aimasso, Umberto; Bioletto, Fabio; Ossola, Marta; Ponzo, Valentina; Goitre, Ilaria; Palermo, Marta; Olimpio, Elisa; Silveri, Stefano; Bo, Simona (Frontiers in Nutrition, 2025)
BackgroundA great heterogeneity exists among patients with chronic intestinal failure even with the same intestinal circuit. Weaning from parenteral support depends on intestinal adaptation, remnant bowel length, and functional capacity. The present study aimed to assess if pre-existent nutritional reserves would predict the possibility of enteral autonomy.MethodsThis retrospective observational study evaluated the incidence of weaning off parenteral support in adult patients with chronic intestinal failure due to short bowel syndrome from an Italian referral center. Multivariable models, considering mortality as a competing risk, identified predictors of weaning.ResultsOut of 251 patients, 116 (46.2%) died without being weaned and 76 (30.3%) were weaned off. The latter showed increased residual small bowel length, more frequently the colon-in-continuity and the ileocecal valve, lower age, higher weight and BMI (25.3 ± 5.6 vs 20.9 ± 3.2 kg/m2) at parenteral support starting. In a multivariable competing risk model, age [sub-distribution hazard ratio (SHR) 0.82; 95%CI 0.71–0.95], small bowel length (SHR = 1.11; 1.06–1.15), type 2 (SHR = 2.63; 1.37–5.02) and type 3 short bowel syndrome (SHR = 6.85; 3.45–13.60), and BMI at enrolment (SHR = 1.11; 1.06–1.15) were significantly associated with weaning off. Body composition by bioelectrical impedance was assessed in a subgroup (n = 147). Patients who weaned displayed increased intracellular water as total water percentage, phase angle and muscle mass index. At multivariable analyses, % intracellular water was a significant predictor of weaning (SHR = 1.06; 1.03–1.09).ConclusionPatients with chronic intestinal failure due to short bowel syndrome with increased BMI and a healthier body composition were more likely to be weaned off parenteral nutrition.